Economic uncertainty and corruption: Evidence from public and private firms - Afzali, Mansoor; Ҫolak, Gönül; Fu, Mengchuan (Journal of Financial Stability, 2021)
We study the influence of policy uncertainty on the moral behavior of firms. When facing uncertainty, managers perceive various socioeconomic obstacles as more severe and disruptive to their business. Using data from policy uncertainty spouts in 93 countries, we document that some firms engage in norm-deviant behavior by cheating on taxes and paying more bribes. While private firms prefer to cheat on taxes, public firms choose bribery as a favorite tool to “grease the wheels” during periods of uncertainty. Strong social capital (local trust and religiosity) breaks this link between uncertainty and corruption.